The tumor suppressor effect of miRNA 200-c-3p on A549 non-small cell lung cancer cell line is associated with down-regulation of programmed cell death ligand 1; an immune-check point mechanism: MiRNA 200-c-3p in A 549 non-small cell lung cancer cell line - Ezzat, Sara; Magda I Mohamad; Manal Basyouni Ahmed; Sara Elsayed Abdelrahman; Nesma Hussein Abdel hay; Nashwa El-Khazragy; Maha Imam Ismail (Cellular and Molecular Biology, 2024)
MiRNA 200-c-3p has varying functions in different tumor types, whether tumor suppression or promotion. Comprehensive assessment of its function in non-small cell lung cancer (NSCLC) together with its effect on antitumor immune response have not been declared before. We aimed to explore the effect of replacement and suppression of miRNA 200-c-3p on (NSCLC) and its impact on immune checkpoint function and subsequently antitumor immunity. MiRNA 200-c-3p mimic/inhibitor was transfected into the A549 (NSCLC). A 549 non-small cell lung cancer cells viability was done by trypan blue staining and 3-(4, 5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. Flowcytometric analysis was done for apoptosis detection. Real‐time reverse transcription-quantitative polymerase chain reaction (RT-qPCR) and western blot analysis were used to study its effect on relative gene expression and relative protein level of programmed cell death ligand 1 (PD-L1). Finally, co-culture with isolated and activated T cells was performed. Multiple comparisons were performed using one-way analysis of variance (ANOVA) followed by Tukey’s multiple-comparison test. Decreased cell viability, increased apoptosis, reduced PD-L1 relative gene expression and its relative protein level, together with enhanced T cell cytotoxicity towards tumor cells were detected after miRNA 200-c-3p mimic transfection of A549 NSCLC cell line. However, these results were reversed in miRNA 200-c-3p suppression. MiRNA 200-c-3p had a tumor suppressive effect in non-small cell lung cancer cells which might be through down regulation of PD-L1 relative gene expression, and it may be used as a new target to improve immune checkpoint dysfunction.